Comparative Studies of Dynamic Mechanical Properties of Desert Sand Concrete and Ordinary Concrete. (10th February 2022) - Chen, Qiaoli; Liu, Haifeng; Han, Li; Wang, Yiying
Abstract : Ningxia is located in the western part of China, which abounds with desert resources. The application of desert sand in concrete has not been fully studied. In order to study the failure mechanism of desert sand concrete under impact loading, dynamic impact experiments on desert sand concrete and ordinary concrete were carried out by using the 74 mm diameter split Hopkinson pressure bar (SHPB) experimental apparatus. The dynamic mechanical properties of desert sand concrete under different impact velocities were analyzed. The random distribution program of round coarse aggregate in desert sand concrete was designed to generate the random distribution of coarse aggregate by ANSYS/APDL language. The dynamic failure process of single-graded concrete and two-graded concrete was numerically simulated and compared. The results showed that desert sand concrete and ordinary concrete have obvious rate-dependent effect. Detailedly, the ordinary concrete is totally destroyed when impact velocity is 10 m/s, but the desert sand concrete still maintains the cone shape at impact velocity of 18 m/s, which indicates that the impact resistance of desert sand concrete is better than that of ordinary concrete. When impact velocity is 5 m/s, the single-graded concrete and two-graded concrete are both destroyed, but the desert sand concrete is not damaged. When impact velocity is 10 m/s, the dynamic failure mode of single-graded concrete, two-graded concrete, and desert sand concrete is basically the same. When impact velocity is 15 m/s, the single-grade concrete shows different dynamic failure mode from that of desert sand concrete and two-graded concrete.